Productive Age Couple’s and Society’s Perception on Vasectomy in Mojokerto Regency of East Java Province - Fibriana, Linda Presti; Oepomo, Tedjo Danudjo; Suminah, Suminah Suminah; Subijanto, Achmad Arman (Advances in Social Sciences Research Journal, 2017)
ABSTRACT Productive Age Couple’s and Society’s Perception on Vasectomy in Mojokerto Regency of East Java Province Author’s Linda Presti Fibriana(1), Tedjo Danudjo Oepomo(2), Suminah(3), AA Subiyanto(4) 1)Development Extension and Community Empowerment Study Program of Health Promotion Concentration, Surakarta Sebelas Maret University 2)Medical Faculty, Surakarta Sebelas Maret University 3)Agricultural Science Study Program, Surakarta Sebelas Maret University 4)Master of Family Medicine, Surakarta Sebelas Maret University Background: Indonesia is the state with the fourth densest population and growth rate of 1.49 percent per year. A large number of people with poor knowledge and inadequate skill become a challenge in issues related to national development. Generally, the result of Family Planning Program among Indonesian women has been successful, in which about 60 percents of participants were women. Fear and anxiety is the main reason of why men have varying perceptions on vasectomy. There is also a false perception sometimes making husband hesitant and decide not to undertake vasectomy. It is because of inadequate general information and knowledge on vasectomy and its side effect on the men’s physical, psychological and social aspects. The objective of research was to explore the productive age couple having undertaken vasectomy and community’s perception on vasectomy in Mojokerto Regency of East Java Province. Subjects and Method: The research method employed was qualitative one with ground theory approach. The sample was taken using theoretical sampling technique. The instruments of collecting data used were field report, audio recording, video recording, and field note. The data was analyzed using Colaizzi method. Results: The result of research was obtained from 10 informants participating in this research. The participants’ reasons of deciding to undertake vasectomy are their social responsibility, feeling of pity to their wife, and caring about their children’s welfare in the future. Generally, there is no change seen on the participants’ physique. Sexual ability after vasectomy operation showed no change. Social perception on vasectomy is varying. Most people believe that having child is important and that family wellbeing is important as well. Conclusion: The participants felt no significant physical change having undertaken vasectomy. They decided to undertake vasectomy to show their love to their wife, responsibility for family wellbeing and children in the future. Therefore, undertaking vasectomy could improve the quality of marriage relationship. Keywords: vasectomy, perception, productive age couple, society Correspondence: Linda Presti Fibriana, Doctoral Program in Health Promotion/ Community Empowerment, Sebelas Maret University, Jl. Ir. Sutami 36A, Surakarta, 57126, Central Java. Email: linda.fibriana@yahoo.com Mobile: 081330569663